2019
DOI: 10.1155/2019/9094178
|View full text |Cite
|
Sign up to set email alerts
|

Safety and Long-Term Efficacy of Drug-Coated Balloon Angioplasty following Rotational Atherectomy for Severely Calcified Coronary Lesions Compared with New Generation Drug-Eluting Stents

Abstract: Objectives. This study sought to assess the safety and long-term efficacy of drug-coated balloons (DCB) following aggressive intracoronary image-guided rotational atherectomy (iRA) for severe coronary artery calcification (CAC), and to compare this strategy with new generation drug-eluting stents (nDES) following iRA. Background. Ischemic events following the treatment of CAC is still relatively high. Thus, more innovative strategies are required. Methods. We evaluated 123 consecutive patients (166 lesions) wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(16 citation statements)
references
References 22 publications
3
13
0
Order By: Relevance
“…RA + DCB results reported in 2017 by Rissanen showed an extremely low TLR rate (1.5% at 12 months) [19]. Subsequently, some studies in Japan also showed a TLR of 6-16%, which was similar to this data [14,20,21]. In Japan, high TLR rate was observed using follow-up CAG.…”
Section: Discussionsupporting
confidence: 77%
“…RA + DCB results reported in 2017 by Rissanen showed an extremely low TLR rate (1.5% at 12 months) [19]. Subsequently, some studies in Japan also showed a TLR of 6-16%, which was similar to this data [14,20,21]. In Japan, high TLR rate was observed using follow-up CAG.…”
Section: Discussionsupporting
confidence: 77%
“…A recent study reported that TLR rates after drug-coated balloon angioplasty following rotational atherectomy for heavily calcified lesions was comparable to that of newergeneration DES. 35 Therefore, if appropriate lesion preparation with rotational atherectomy is achieved in heavily calcified lesions with CN, a "stentless" strategy using drugcoated balloons could be an alternative treatment choice. Furthermore, considering the inferior outcomes of target lesions with CN, detection of CNs in multivessel heavily calcified lesions may encourage the referral of patients for coronary artery bypass grafting rather than performing multiple PCI procedures.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, several recent reports have indicated that stentless PCI using RA/DCB could also be a revascularization therapy of choice particularly for calcified lesions. 1 , 2 , 3 , 4 In contrast, the role of RA for noncalcified lesions in the current DES era still remains uncertain. According to previous reports in the pre-stent era, RA effectively debulked even noncalcified lesions on intravascular ultrasound imaging, and the procedural initial success rate of RA did not differ between noncalcified and calcified lesions.…”
Section: Discussionmentioning
confidence: 99%
“…Recently drug-coated balloon (DCB)-only angioplasty for de novo lesions has attracted greater attention, and pretreatment with rotational atherectomy (RA) followed by DCB treatment (RA/DCB) has been reported to be an option of stentless PCI particularly for calcified de novo lesions. 1 , 2 , 3 , 4 However, even small-sized data regarding the RA/DCB procedure for noncalcified de novo lesions are still lacking. The purpose of the present retrospective study was therefore to compare angiographic results and clinical outcomes in patients with noncalcified de novo lesions who underwent RA/DCB with patients with calcified de novo lesions in a real-world clinical practice.…”
mentioning
confidence: 99%